The Development and Evaluation of a New ASL Text Comprehension Task - Rosenburg, Patrick; Lieberman, Amy M.; Caselli, Naomi; Hoffmeister, Robert (Frontiers in Communication, 2020)
Work in literacy education over the past two decades has radically shifted the notion of literacy, broadening it to include the ability to engage with compositions in various media (e.g., not only traditional texts like books and articles but also vlogs, blogs, graphic novels etc.). The notion that literacy can apply to non-written compositions has led some to wonder about the development of “reading comprehension” of texts in languages like American Sign Language (ASL) that do not have a written form. However, there are no existing assessments of ASL text comprehension. In this paper, we introduce the ASL-CMP, a new assessment tool to measure American Sign Language (ASL) text comprehension ability in deaf children. We first administered the task to a group of deaf children with deaf parents (n = 105, ages 8-18 years) in order to evaluate the reliability and validity of the task, and to develop norms. We found that the ASL-CMP has acceptable levels of internal consistency, difficulty, and discriminability. Next, we administered the task to an additional group of deaf children with hearing parents (n = 198, ages 8-18 years), and found that the ASL-CMP is sensitive to expected patterns: older children have better ASL text comprehension skills, literal questions are generally easier to answer than inferential questions, and children with early exposure to ASL generally outperform those with delayed exposure. We conclude that the ASL-text comprehension task is reliable and valid and can be used to characterize comprehension skills in ASL in deaf children ages 8-12.